Intraoperative Conversion to ALPPS in a Case of Intrahepatic Cholangiocarcinoma - F. Oldhafer; K. I. Ringe; K. Timrott; M. Kleine; W. Ramackers; S. Cammann; M. D. Jäger; J. Klempnauer; H. Bektas; F. W. R. Vondran (Case Reports in Surgery)
Background. Surgical resection remains the best treatment option for intrahepatic cholangiocarcinoma (ICC). Two-stage liver resection combining in situ liver transection with portal vein ligation (ALPPS) has been described as a promising method to increase the resectability of liver tumors also in the case of ICC. Presentation of Case. A 46-year-old male patient presented with an ICC-typical lesion in the right liver. The indication for primary liver resection was set and planed as a right hepatectomy. In contrast to the preoperative CT-scan, the known lesion showed further progression in a macroscopically steatotic liver. Therefore, the decision was made to perform an ALPPS-procedure to avoid an insufficient future liver remnant (FLR). The patient showed an uneventful postoperative course after the first and second step of the ALPPS-procedure, with sufficient increase of the FLR. Unfortunately, already 2.5 months after resection the patient had developed new tumor lesions found by the follow-up CT-scan. Discussion. The presented case demonstrates that an intraoperative conversion to an ALPPS-procedure is safely applicable when the FLR surprisingly seems to be insufficient. Conclusion. ALPPS should also be considered a treatment option in well-selected patients with ICC. However, the experience concerning the outcome of ALPPS in case of ICC remains fairly small.